2010
DOI: 10.1038/ijo.2010.148
|View full text |Cite
|
Sign up to set email alerts
|

Use of self-reported height and weight biases the body mass index–mortality association

Abstract: Background Many large-scale epidemiologic data sources used to evaluate the body mass index (BMI: kg/m2) mortality association have relied on BMI derived from self-reported height and weight. Although measured BMI (BMIM) and self-reported BMI (BMISR) correlate highly, self-reports are systematically biased. Objective To rigorously examine how self-reporting bias influences the association between BMI and mortality rate. Subjects Samples representing the US non-institutionalized civilian population. Desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
85
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(91 citation statements)
references
References 45 publications
(102 reference statements)
4
85
0
2
Order By: Relevance
“…Although correlations between self-reported and measured values of these variables are usually strong, systematic errors according to sex, ethnicity, and overweight status have been reported [3739]. One study in nationally representative U.S. samples assessed the BMI-mortality association using both self-reported and measured weight and height, and demonstrated that BMI based on self-reported values led to underestimation of the association for underweight and overestimation of the association for obesity [40]. Furthermore, long-term recall of weight at age 21 may be further error-prone.…”
Section: Discussionmentioning
confidence: 99%
“…Although correlations between self-reported and measured values of these variables are usually strong, systematic errors according to sex, ethnicity, and overweight status have been reported [3739]. One study in nationally representative U.S. samples assessed the BMI-mortality association using both self-reported and measured weight and height, and demonstrated that BMI based on self-reported values led to underestimation of the association for underweight and overestimation of the association for obesity [40]. Furthermore, long-term recall of weight at age 21 may be further error-prone.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly pertinent to this review, maternal obesity is associated with gestational complications and adverse fetal and neonatal health outcomes (348,513). However, there remains a controversy as to the higher rate of mortality among the overweight and obese, particularly using selfreported BMI (244). Some report the so-called obesity paradox whereby the overall mortality was lower among those with T2DM and cardiovascular comorbidity and weight loss but not weight gain was associated with increased mortality and morbidity (124,125).…”
Section: B Prevalence and Associated Morbidity And Mortality Of Obesitymentioning
confidence: 99%
“…Finally, we included only men in this study, thereby the generalization of our results to women was limited. The strengths of this study include the standardized and direct (rather than reported) measurements of height and weight (36), strict followup, and careful adjustment to other CAD risk factors.…”
Section: Discussionmentioning
confidence: 99%